The boundary flux handbook : a comprehensive database of critical and threshold flux values for membrane practitioners - Stoller, Marco; Ochando-Pulido, Javier Miguel (Elsevier Ltd., 2015)
The Boundary Flux Handbook summarizes over 100 chemical compounds (single compounds, in mixed solution) and different feed streams from industry (complex streams exiting the agricultural, biological, pharmaceutical, food, dye, textile, and other industries) and the respective critical and threshold fluxes (or boundary flux), together with data on rejection and permeabilities. It gives the reader valuable data to quickly estimate membrane performances in respect to productivity, selectivity, and longevity, and aids in estimating capital and operating costs of membrane processes during the plan.